IMPLEMENTASI PRAKTIK KERJA INDUSTRI DI SMK NEGERI 1 SOPPENG - Husain AS; Elpisah .; Muh. As'ad (STKIP Pembangunan Indonesia Makassar, 2019)
This study examines the implementation of industrial work practice programs (Prakerin/ Workmanship) at SMK Negeri 1 Soppeng. The purpose of this research is to find out the planning, organizing, implementing, and supervising industrial work practices at Soppeng Vocational School 1. This research will benefit the implementation and development of industrial work practices, especially the apprenticeship managers, namely principals, teachers, and the business world/industrial world. This study uses descriptive qualitative method to analyze the implementation of industrial work practice programs at SMK Negeri 1 Soppeng. The sources of data in this study are the Principal, teachers, students, alumni, and the business world/industrial world. Data collection in this study is by interview, observation, and documentation. The data analysis techniques are data reduction, data presentation, conclusions and verification. The results of this study indicate that the planning of industrial work practices at SMK Negeri 1 Soppeng has been running in accordance with the objectives to be achieved. Organizing industrial work practices at Soppeng 1 State Vocational School is in accordance with school organization standards. The implementation of industrial work practices at SMK Negeri 1 Soppeng is carried out well and optimally. While the supervision of industrial work practices at SMK Negeri 1 Soppeng involves school stakeholders so that it is well implemented, especially regarding the suitability and quality of students with the competencies that have been owned at the time of implementation of the business practice in the business/industrial world.Keywords: Implementation, Prakerin/Workmanship, planning, organization, actuation, and supervision